PERAN AYAH ASI DALAM KEBERHASILAN PEMBERIAN ASI EKSKLUSIF - Annisa Nurhayati Hidayat; Indah Nurfazriah (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Breastmilk (ASI) is the best food for babies, which contains white blood cells, protein and immune substances suitable for babies. Breast milk helps the child's optimal growth and development and protects against disease. Whereas in Banten Province in 2018, the percentage of exclusive breastfeeding was 62.79% (Riskesdas, 2018). Several factors can influence mothers to exclusive breastfeeding their babies. One of them is the support from the husband, who plays a role in the success of breastfeeding mothers. Husbands can be the key to success in exclusive breastfeeding for their children if the husbands carry out their roles properly. The research objective is to determine the relationship between the father's role in breastfeeding and the success of exclusive breastfeeding in the working area of the Ciomas Public Health Center in 2020. Methods: The type of research used is quantitative with a descriptive-analytic design through a cross-sectional approach. The research was carried out in the Working Area of the Ciomas Health Center in September - October 2020. The sample in the study was 30 respondents who had babies over 6-24 months with a consecutive sampling technique. Retrieval of data using questionnaires online. The analysis used was the Spearman rank (rho) correlation test method. The results of the study showed that out of 10 people who had a good father role, nine people (90%) succeeded in exclusive breastfeeding with good knowledge, three people (75%) and 20 people were included in the category of poor father role, 18 people did not succeed in breastfeeding. Exclusive (90%) with a p-value <0.05 indicates a significant relationship between the role of fathers and the success of exclusive breastfeeding. With the criteria of a strong relationship of 0.783, it is included in the very strong category (0.76 - 0.99)